Analysis of global upstream oil and gas assets deal characteristics and regional influencing factors. Issue 1 (March 2020) - Zou, Qian; Wang, Keming; Yin, Xiuling; Peng, Min
Abstract: With the sustained decline and slow recovery of international oil prices, the global upstream oil & gas deal market has witnessed significant changes since 2014. Generally, five characteristics were present: (1) shrinking deal count, (2) dominance in North America tight oil, (3) matching deals and asset optimization strategy for oil giants, (4) sluggish deals of national oil companies, and (5) active deals of small oil companies and other investors. From the regional perspective, in North America, the deals in the Permian Basin remain active; in Latin America, the deals are dominated by asset disposal and deepwater tender; in Asia-Pacific, gas-related deal count rebounded after bottoming out; in Russia-Central Asia, asset sale is subject to the domestic financial situation; in Africa, the deal count hovers at a low level; in the Middle East, the market will be open. In 2019, as the oil price rises from a stable level, the deal upsurge will unfold again, and the unconventional oil & gas industry in the United States will be continuously integrated. Then, diversified players and extensive transaction opportunities can be expected on the oil & gas market.